Alzheimer disease sourcebook : basic consumer health information about Alzheimer disease and other forms of dementia, including mild cognitive impairment, corticobasal degeneration, dementia with Lewy bodies, frontotemporal dementia, Huntington disease, Parkinson disease, and vascular dementia along with information about recent research on the diagnosis and prevention of Alzheimer disease and genetic testing, tips for maintaining cognitive functioning, strategies for long-term planning, advice for caregivers, a glossary of related terms, and directories of resources for additional help and information - Sutton, Amy L. (Detroit, Mich. : Omnigraphics, 2011)
"Provides basic consumer health information about symptoms, diagnosis, and treatment of Alzheimer disease and other dementias, along with tips for coping with memory loss and related complications and advice for caregivers. Includes index, glossary of related terms and directory of resources"--Provided by publisher.
15: Other factors that influence AD risk: -- 15-1: Alcohol abuse linked to AD and dementia -- 15-2: Secondhand smoke -- 15-3: Heart health -- Part 3: Other Dementia Disorders: -- 16: Mild cognitive impairment -- 17: Degenerative neurological disease -- 17-1: Corticobasal degeneration -- 17-2: Dementia with lewy bodies -- 17-3: Frontotemporal dementia -- 17-4: Huntington disease -- 17-5: Parkinson disease -- 18: Vascular dementia: -- 18-1: What is vascular dementia? -- 18-2: Binswanger disease (subcortical vascular dementia) -- 18-3: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) -- 18-4: Multi-infarct dementia -- 19: Dementia caused by infection: -- 19-1: Creutzfeldt-Jakob disease -- 19-2: Acquired immunodeficiency syndrome (AIDS) dementia complex -- 20: Other health conditions that cause dementia: -- 20-1: Cancer, delirium, and dementia -- 20-2: Dementia: a symptom of normal pressure hydrocephalus -- Part 4: Recognizing, Diagnosing, And Treating Symptoms Of AD And Dementias: -- 21: Forgetfulness: knowing when to ask for help -- 22: Talking with your doctor -- 23: Diagnosing AD -- 23-1: How is AD diagnosed? -- 23-2: AD guidelines updated for first time in decades -- 24: Testing for AD -- 24-1: Mental status tests -- 24-2: Positron Emission Tomography (PET) and Single Photon Emission Computed Tomography (SPECT) -- 24-3: Magnetic Resonance Imaging (MRI) -- 24-4: ApoE genotyping -- 24-5: Biomarker testing for AD: checking for Tau protein and Amyloid Beta 42 in cerebrospinal fluid -- 25: Overview of AD interventions -- 26: AD medications -- 27: Medications for cognitive changes -- 28: Participating in AD clinical trials and studies -- 29: Can AD be prevented? -- 30: Recent AD research -- 30-1: Amyloid deposits may predict risk for AD -- 30-2: Ovary removal may increase risk of dementia -- 30-3: Changes occur in high-risk seniors before AD symptoms appear -- 30-4: Family with AD may carry clues to treatment -- 30-5: Insulin may improve memory in people with AD -- Part 5: Living With AD And Dementias: -- 31: Talking about your diagnosis: -- 31-1: Telling others about an AD diagnosis -- 31-2: Talking to children about AD -- 32: Getting support for AD and dementia -- 33: Preventing cognitive decline if you have AD or dementia -- 34: Nutrition, exercise, and therapeutic recommendations -- 34-1: Questions and answers about AD, diet, and exercise -- 34-2: Physical activity benefits nursing-home residents with AD -- 34-3: Alternative medicine therapies for AD and dementia -- 35: Dental care and the dementia patient -- 36: Hearing loss, AD, and dementia -- 37: Pain and dementia -- 38: Sexuality and AD -- 39: Sleep problems and dementia -- 39-1: Treatment for dementia-related sleep changes -- 39-2: Light therapy -- 40: Driving and dementia -- 41: Living alone with AD or dementia -- 42: Financial concerns and AD -- 43: Medicare and AD -- 43-1: Understanding Medicare -- 43-2: Choosing a Medicare drug plan for people with AD -- 43-3: Medicare's hospice benefit for people with AD -- 44: Getting your affairs in order -- 44-1: Planning for the future -- 44-2: Elder law attorneys -- 44-3: Legal and health care planning documents -- 44-4: Making end-of-life choices -- Part 6: Caregiver Concerns: -- 45: Caring for a person with AD or dementia -- 46: Long-distance caregiving -- 47: Coping with challenging behaviors -- 47-1: Understanding challenging behaviors -- 47-2: Depression and anxiety often present in people with dementia -- 48: Techniques for communicating with someone with dementia -- 49: Planning the day for someone with dementia -- 50: Safety issues for people with AD -- 50-1: Safety at home -- 50-2: MedicAlert and the Safe Return Program -- 50-3: Caring for someone with dementia in a disaster -- 50-4: Understanding elder abuse -- 51: Dementia, caregiving, and controlling frustration -- 52: Respite care: giving caregivers a break -- 53: Hiring in-home care providers -- 54: Choosing a nursing home -- 55: Hospitalization and AD -- 56: Making decisions about resuscitation -- 57: Making tube feeding decisions for people with advanced dementia -- 58: Caring for someone near the end of life -- Part 7: Additional Help And Information: -- 59: Glossary of terms related to AD and dementia -- 60: Directory of resources for people with dementia and their caregivers -- 61: Alzheimer Disease Centers (ADCs) program directory -- Index.: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) -- 18-4: Multi-infarct dementia -- 19: Dementia caused by infection: -- 19-1: Creutzfeldt-Jakob disease -- 19-2: Acquired immunodeficiency syndrome (AIDS) dementia complex -- 20: Other health conditions that cause dementia: -- 20-1: Cancer, delirium, and dementia -- 20-2: Dementia: a symptom of normal pressure hydrocephalus -- Part 4: Recognizing, Diagnosing, And Treating Symptoms Of AD And Dementias: -- 21: Forgetfulness: knowing when to ask for help -- 22: Talking with your doctor -- 23: Diagnosing AD -- 23-1: How is AD diagnosed? -- 23-2: AD guidelines updated for first time in decades -- 24: Testing for AD -- 24-1: Mental status tests -- 24-2: Positron Emission Tomography (PET) and Single Photon Emission Computed Tomography (SPECT) -- 24-3: Magnetic Resonance Imaging (MRI) -- 24-4: ApoE genotyping -- 24-5: Biomarker testing for AD: checking for Tau protein and Amyloid Beta 42 in cerebrospinal fluid -- 25: Overview of AD interventions -- 26: AD medications -- 27: Medications for cognitive changes -- 28: Participating in AD clinical trials and studies -- 29: Can AD be prevented? -- 30: Recent AD research -- 30-1: Amyloid deposits may predict risk for AD -- 30-2: Ovary removal may increase risk of dementia -- 30-3: Changes occur in high-risk seniors before AD symptoms appear -- 30-4: Family with AD may carry clues to treatment -- 30-5: Insulin may improve memory in people with AD -- Part 5: Living With AD And Dementias: -- 31: Talking about your diagnosis: -- 31-1: Telling others about an AD diagnosis -- 31-2: Talking to children about AD -- 32: Getting support for AD and dementia -- 33: Preventing cognitive decline if you have AD or dementia -- 34: Nutrition, exercise, and therapeutic recommendations -- 34-1: Questions and answers about AD, diet, and exercise -- 34-2: Physical activity benefits nursing-home residents with AD -- 34-3: Alternative medicine therapies for AD and dementia -- 35: Dental care and the dementia patient -- 36: Hearing loss, AD, and dementia -- 37: Pain and dementia -- 38: Sexuality and AD -- 39: Sleep problems and dementia -- 39-1: Treatment for dementia-related sleep changes -- 39-2: Light therapy -- 40: Driving and dementia -- 41: Living alone with AD or dementia -- 42: Financial concerns and AD -- 43: Medicare and AD -- 43-1: Understanding Medicare -- 43-2: Choosing a Medicare drug plan for people with AD -- 43-3: Medicare's hospice benefit for people with AD -- 44: Getting your affairs in order -- 44-1: Planning for the future -- 44-2: Elder law attorneys -- 44-3: Legal and health care planning documents -- 44-4: Making end-of-life choices -- Part 6: Caregiver Concerns: -- 45: Caring for a person with AD or dementia -- 46: Long-distance caregiving -- 47: Coping with challenging behaviors -- 47-1: Understanding challenging behaviors -- 47-2: Depression and anxiety often present in people with dementia -- 48: Techniques for communicating with someone with dementia -- 49: Planning the day for someone with dementia -- 50: Safety issues for people with AD -- 50-1: Safety at home -- 50-2: MedicAlert and the Safe Return Program -- 50-3: Caring for someone with dementia in a disaster -- 50-4: Understanding elder abuse -- 51: Dementia, caregiving, and controlling frustration -- 52
Includes bibliographical references and index.
Keywords: Alzheimer's disease -- Popular works; Dementia -- Popular works; Alzheimer Disease -- Popular Works; Alzheimer Disease -- Resource Guides; Dementia -- Popular Works; Dementia -- Resource Guides